The Interaction Effects of Frequency and Specificity of Feedback on Work Performance. Issue 3 (2nd October 2019) - Park, Jin-A; Johnson, Douglas A.; Moon, Kwangsu; Lee, Jaehee
ABSTRACT: This study investigated the interaction effect between specificity (specific vs. global) and frequency of feedback (frequent vs. infrequent) on the quality of work performance. Eighty participants were recruited and randomly assigned to one of the four groups: specific and frequent feedback, global and frequent feedback, specific and infrequent feedback, and global and infrequent feedback. A 2 × 2 factorial design was adopted. Participants were asked to work on a simulated order-fulfilling task and attended 24 sessions. The dependent variable was the error rate of the completed tasks. The results showed that more frequent feedback was more effective and specific feedback was more effective than global feedback in improving the quality of performance. Furthermore, an interactive effect between feedback frequency and specificity was found. Specific feedback was more effective than global feedback when the feedback was infrequent, but global feedback was comparable to specific feedback when it was frequent.